Angiotensin‐converting enzyme inhibitors stimulate cerebral arteriogenesis. (2nd October 2021) - Hillmeister, Philipp; Nagorka, Stephanie; Gatzke, Nora; Dülsner, Andre; Li, Kangbo; Dai, Mengjun; Bondke Persson, Anja; Lauxmann, Martin A.; Jaurigue, Jonnel; Ritter, Oliver; Bramlage, Peter; Buschmann, Eva; et al.
Abstract: Aim: Arteriogenesis constitutes the most efficient endogenous rescue mechanism in cases of cerebral ischaemia. The aim of this work was to investigate whether angiotensin‐converting enzyme inhibitors (ACEi) stimulates, and angiotensin II receptor type 1 blockers (ARB) inhibits cerebral collateral growth by applying a three‐vessel occlusion (3‐VO) model in rat. Methods: Cerebral collateral growth was measured post 3‐VO (1) by assessing blood flow using the cerebrovascular reserve capacity (CVRC) technique, and (2) by assessing vessel diameters in the posterior cerebral artery (PCA) via the evaluation of latex angiographies. A stimulatory effect on arteriogenesis was investigated for ACEi administration ± bradykinin receptor 1 (B1R) and 2 (B2R) blockers, and an inhibitory effect was analysed for ARB administration. Results were validated by immunohistochemical analysis and mechanistic data were collected by human umbilical vein endothelial cell (HUVEC) viability or scratch assay and monocyte (THP‐1) migration assay. Results: An inhibitory effect of ARB on arteriogenesis could not be demonstrated. However, collateral growth measurements demonstrated a significantly increased CVRC and PCA diameters in the ACEi group. ACEi stimulates cell viability and migration, which could be partially reduced by additional administration of bradykinin receptor 1 inhibitor (B1Ri). ACEi inhibits the degradation of pro‐arteriogenic bradykinin derivatives, but combined ACEi + B1Ri + B1Ri (BRB) treatment did not reverse the stimulatory effect. Yet, co‐administration of ACEi + BRB enhances arteriogenesis and cell migration. Conclusion: We demonstrate a potent stimulatory effect of ACEi on cerebral arteriogenesis in rats, presumable via B1R. However, results imply a pleiotropic and compensatory effect of ACEi on bradykinin receptor‐stimulated arteriogenesis.